2018
DOI: 10.1038/s41598-018-32073-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of endothelial progenitor cell culture under microgravity for improved angiogenic potential

Abstract: Endothelial progenitor cell (EPC) transplantation is beneficial for ischemic diseases such as critical limb ischemia and ischemic heart disease. The scarcity of functional EPCs in adults is a limiting factor for EPC transplantation therapy. The quality and quantity culture (QQc) system is an effective ex vivo method for enhancing the number and angiogenic potential of EPCs. Further, microgravity environments have been shown to enhance the functional potential of stem cells. We therefore hypothesized that cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Previously, altered gravity was identified to regulate oxygen homeostasis and HIF-1-dependent transcripts [ 30 , 31 ], and consequently refine the regenerative potentials of cells similar to hypoxic culture [ 32 ]. In our study, we for the first time found the HIF-1α/eNOS axis was activated by MG within 24 h, partially supporting the previous findings and complementing them [ 22 , 24 , 25 ]. As eNOS-derived NO are mainly regulated by angiogenic effectors or mechanical stress, which are responsible for vascular function maintenance, while iNOS induced NO are by proinflammatory cytokines that are usually involved in vascular pathologic processes [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previously, altered gravity was identified to regulate oxygen homeostasis and HIF-1-dependent transcripts [ 30 , 31 ], and consequently refine the regenerative potentials of cells similar to hypoxic culture [ 32 ]. In our study, we for the first time found the HIF-1α/eNOS axis was activated by MG within 24 h, partially supporting the previous findings and complementing them [ 22 , 24 , 25 ]. As eNOS-derived NO are mainly regulated by angiogenic effectors or mechanical stress, which are responsible for vascular function maintenance, while iNOS induced NO are by proinflammatory cytokines that are usually involved in vascular pathologic processes [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Consistently, the present study also showed that short-term MG exposure significantly attenuated the proliferation of EPCs. However, it is also reported that MG exposure followed by NG culture could improve EPCs’ expansion rates and paracrine properties [ 25 ]. Therefore, MG simulation may be a powerful bioengineering tool for eliciting cell angiogenic potentials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hagiwara et al. showed an interesting application of microgravity culture in vasculogenesis and tissue regeneration [66]. They demonstrated that initial cultivation under microgravity conditions followed by cultivation under a 1G environment was shown to increase endothelial progenitor cell expansion rates and angiogenic potential to a remarkable degree.…”
Section: Microgravity Culture Enhances the Therapeutic Effect Of Stemmentioning
confidence: 99%
“…protocols for the in vitro cultivation and expansion of EPCs have been developed, these techniques still yield insufficient cell numbers and angiogenic potential (Sukmawati, & Tanaka 2015). A recent study (Hagiwara et al, 2018) demonstrated that microgravity stimulation can increase the number and angiogenic potential of CD34+ cells from peripheral blood mononuclear cells (PBMNCs).…”
mentioning
confidence: 99%